Nutrient Utilizations and Intestinal Morphology of Broilers Treated with Lactobacillus plantarum AKK30 – Oligosaccharides Synbiotic - H. Julendra; A. Sofyan; M. F. Karimy; Abinawanto Abinawanto; Yasman Yasman (Tropical Animal Science Journal, 2020)
Lactobacillus plantarum AKK30 inoculum in de Maan Rogosa Sharpe Broth (MRSB) grown on media containing oligosaccharides (inulin or mannan oligosaccharides/MOS) was studied in vitro and in vivo. In vitro assay was conducted to characterize metabolite profiles and its effect on pathogenic bacteria, while in vivo assay was conducted to study the metabolic energy, nitrogen retention, and intestinal morphology of broilers. A total of 24 male broilers-40-day-old (average body weight= 1.725±0.05 kg) strains Cobb-500 were used, where 20 birds were added 1% inoculum L plantarum AKK30 of daily intake and randomly distributed in five treatments and four replications consisted of: A) MRSB + L. plantarum AKK-30 (10⁷ cfu g-1); B) MRSB + inulin 0.5% (w v-1); C) MRSB + MOS 0.5%(w v-1); D) L. plantarum AKK-30 (10⁷ cfu g-1) + MRSB + inulin 0.5% (w v-1).; and E) L. plantarum AKK-30 (10⁷ cfu g-1) + MRSB + MOS 0.5% (w v-1), while 4 birds were fasted as endogenous chicken. The results showed that the highest isoleucine and threonine were found in group E. The highest oleic acid and the lowest conjugated linoleic acid (CLA) were observed in all treatments and inoculum did not affect antibacterial activity. The metabolizable energy values and nitrogen retention in group D and E were higher than other treatments (p<0.05). The lowest height of villi was observed in group A (p<0.05). In conclusion, the addition of oligosaccharides inulin or mannan oligosaccharide (MOS) affects the metabolite profiles of Lactobacillus plantarum AKK30 and their synbiotic effects improve intestinal morphology, metabolizable energy, and nitrogen retention in broilers.